2014
DOI: 10.1021/jp505346g
|View full text |Cite
|
Sign up to set email alerts
|

EPR Line Shifts and Line Shape Changes Due to Heisenberg Spin Exchange and Dipole–Dipole Interactions of Nitroxide Free Radicals in Liquids: 9. An Alternative Method to Separate the Effects of the Two Interactions Employing 15N and 14N

Abstract: A method to separate the effects of Heisenberg spin exchange (HSE) and dipole–dipole (DD) interactions on EPR spectra of nitroxide spin probes in solution by employing 15N and 14N nitroxide spin probes in parallel experiments is developed theoretically and tested experimentally. Comprehensive EPR measurements are reported of 4-oxo-2,2,6,6-tetramethylpiperidine-d16;1-15N-1-oxyl (perdeuterated 15N Tempone; 15pDT), in 70 wt % aqueous glycerol as functions of concentration and temperature. The method, termed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Moving from top to bottom in Figure B as the samples change from low to high nitroxide concentrations, the spectra become increasingly broadened. This broadening is due to Heisenberg spin exchange as neighboring electrons with identical spin states are close enough to swap their spin information at a rate that is much faster than the rate of the inverse of the hyperfine interactions . In going from lower to higher temperatures at intermediate concentrations, the line shapes sharpen at higher temperatures as a result of motional narrowing.…”
Section: Results and Discussionsupporting
confidence: 84%
“…Moving from top to bottom in Figure B as the samples change from low to high nitroxide concentrations, the spectra become increasingly broadened. This broadening is due to Heisenberg spin exchange as neighboring electrons with identical spin states are close enough to swap their spin information at a rate that is much faster than the rate of the inverse of the hyperfine interactions . In going from lower to higher temperatures at intermediate concentrations, the line shapes sharpen at higher temperatures as a result of motional narrowing.…”
Section: Results and Discussionsupporting
confidence: 84%
“…Standard relations imply that the HSE and DDI contributions to the coefficient W j can be separated by defining H j = ( b j W j + V j )/(1/ j + b j ) and D j = W j – H j , where b 1 = 2/7 for 15 N-pDTEMPONE and b 2 = 4/19 for 14 N-pDTEMPONE . It can be easily shown that H j = W j HSE and D j = W j DD when eq holds.…”
Section: Resultsmentioning
confidence: 90%
“…[1, 68, 1113] Here, the results are far more interesting than for 15 N, because there are differences between the exact and perturbation results for every parameter. We have not been able to find any simple relationships between the exact and perturbation results similar to that in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…[1, 68, 1113] All entries given as fractions In Tables 2 – 5 are exact to within ±1 in the least significant of 16 digits. Comparing Tables 2 and 3 highlights the fact that values of V pp± 1 and Δ H pp± 1 are identical for the absorption components and their perturbation counterparts, but only to 5 significant figures; in fact, the largest difference is 5 x 10 −16 .…”
Section: Resultsmentioning
confidence: 99%